Expert system for real time optimization of solid waste management in Malaysia - Abu Samah, Mohd Armi (2014)
As in every developing nation, increasing revenues in urban areas attract masses of population to move to these areas which indirectly increase the rate of solid waste generated. Malaysia being one the developing countries in South East Asia also faces the same problem due to the lack of comprehensive data and public awareness towards this issue. Hence a novel expert system using combination of Linear Model as the engine and the IF-THEN rule concepts was created to predict rate of solid waste generated so that users could be given advices and appropriate steps to be taken regarding integrated solid waste management. The system, named OpSWaste was designed based on information from journals and /or interview sessions conducted with known experts within the field. Users of this system only have to separate their solid waste materials into different categories according to the system requirement. From the processed data, users could obtain amount of solid waste produced in each categories and appropriate actions could be taken to optimize the waste materials. Samples of solid waste were collected from Balakong, Selangor and they were used to test and validate the operation and function of this system. From the sampling done, it was found that the actual waste composition generated for a month in residential, shopping and industrial area in Balakong was approximately 5,344.00 kg, 9067.90 kg,864.95 kg, respectively. Based on this data, OpSWaste system processed and produced an output forecasting that within 12 months the amount of solid waste generated at residential, shopping and industrial areas would be 8,555.92 kg, 14,516.56 kg and 1,384.81 kg respectively. Moreover, this system could be applied by a particular user in determining preliminary module for recycling process and could controlled and optimized the amount of generated waste composition that were usually sent to the landfills or other waste treatment facilities. OpSWaste system also integrates Life Cycle Assessment (LCA) which involves evaluation process of inputs and outputs of material, energy and waste flows associated with a recycling product over its entire life cycle. Overall, the output of OpSWaste could predict waste generation growth, revenue from recycling and give out recycling process options in real time basis. OpSWaste system could be applied together with other systems such as URUS SISA, being similar but only focused on the selection of treatment technology based on Analytical Hierarchy Process (AHP) that could be divided into three hierarchy level; objective, criteria and alternatives. In conclusion, the integration of OpSWaste could help to make prompt decision based solely on accurate amount of solid waste composition taken from collectors’ to enable better decision making among policies makers, stakeholders and relevant agencies in solving the problem of solid waste management in Malaysia.